2013
DOI: 10.1007/s12017-013-8224-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multifactorial Nature of Autism Through Computational Systems Biology: Calcium and the Rho GTPase RAC1 Under the Spotlight

Abstract: Autism is a neurodevelopmental disorder characterized by impaired social interaction and communication accompanied with repetitive behavioral patterns and unusual stereotyped interests. Autism is considered a highly heterogeneous disorder with diverse putative causes and associated factors giving rise to variable ranges of symptomatology. Incidence seems to be increasing with time, while the underlying pathophysiological mechanisms remain virtually uncharacterized (or unknown). By systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 138 publications
8
54
0
3
Order By: Relevance
“…Several other autism-risk genes, such as Nlg1, Nrx-4, P-Rex1, and Shank-3, have also been reported to participate in the Rac1-signaling pathway (61)(62)(63)(64). In addition, when the gene-environment interactions of 122 genes and 191 factors in the autistic context were analyzed by systems biology, Rac1 was predicted to be a converging node that genetically links to the neurobiology of autism (27,65)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other autism-risk genes, such as Nlg1, Nrx-4, P-Rex1, and Shank-3, have also been reported to participate in the Rac1-signaling pathway (61)(62)(63)(64). In addition, when the gene-environment interactions of 122 genes and 191 factors in the autistic context were analyzed by systems biology, Rac1 was predicted to be a converging node that genetically links to the neurobiology of autism (27,65)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inability to evoke Rac1-dependent forgetting causes behavioral inflexibility in transgenic flies, and the inability to forget may cause behavioral inflexibility in autism patients. Second, a systems biology analysis concludes that Rac1 plays a critical role in the neuropathological events associated with autism based on gene-expression analysis of cerebellar samples from patients with autism (27). Thus, we were led to investigate whether Rac1-dependent forgetting is a converging function of homologs of autism-risk genes.…”
mentioning
confidence: 99%
“…Guerin et al 10 described a single patient with a 2.89-Mb deletion in distal 11q who had autistic features and proposed the Kirrel3 gene as a candidate for causing autism in the patient. ASD results from a large variety of genetic causes 30,31 and the results from the current study add to the growing list of genetic syndromes associated with a proportion of children who have ASD. 32 Original research article…”
Section: Discussionmentioning
confidence: 61%
“…35 ARHGAP32 (formerly RICS) encodes a neuronassociated GTPase-activating protein that regulates dendritic spine morphology and strength by modulating Rho GTPase. 31,36 Studies of mice revealed that ARHGAP32 is involved in early brain development, including extension of axons and dendrites, and postnatal remodeling and fine-tuning of neural circuits. 37 To date, nothing is known about the role of ARHGAP32 in cognition or behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while a role for Ca 2+ ions may be excluded in the reduced dendritic arborization of TS cells, it cannot be disregarded in contributing to the overall autistic phenotype in TS patients. A recent combination of systems and computational approaches suggested Ca 2+ as a central factor in the pathophysiology of autism [54].…”
Section: Nervementioning
confidence: 99%